The Role of Leadership in Reducing Academic Dishonesty - Raynor , Tim (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2017)
The article exams the role of school leadership in reducing academic dishonesty. The research reviewed material on educational leadership, academic tegrity/honor codes, faculty enforcement  of honor codes, faculty perceptions of honor codes, school climate, school culture, student course  evaluations, faculty reactions to student course evaluations and best practices that help reduce academic dishonesty. The role of leadership in combating cheating is extremely important because school leaders can create and promote a positive learning environment that reduces academic dishonesty and improves student learning.